PENGARUH TIPE INDUSTRI, UKURAN PERUSAHAAN, PROFITABILITAS, TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Purwanto, Agus (JURNAL AKUNTANSI DAN AUDITING, 2011)
This study aims to analyze the affect of industry type, company size, and profitability on thecorporate social responsibility in annual reports. Collecting data using a purposive samplingmethod to non-financial companies listed in Indonesia Stock Exchange in 2009. There are 92companies are used as research samples. Hypothesis testing is done with multiple regressionanalysis. This study used independent variable like: industry type, company size, profitability;and so the dependent variable used is corporate social responsibility. The results ofregression models indicate industry type and firm size affect to corporate socialresponsibility. However, company profitability doesn’t affect to corporate socialresponsibility. By the way, that profitability doesn’t have association with the corporatesocial responsibility disclosure.Keywords:corporate social responsibility, industry type, company size, profitability.